Trajektoria trwania opancerzonych demokracji - Bäcker, Roman; Rak, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The theoretical category of militant democracy in Karl Loevenstein’s meaning is described well in world scholarly literature. Notwithstanding, there is no comprehensive typology of militant democracy which would allow for identifying and diversifying various political regimes which meet the distinctive features of the Weberian ideal type of militant democracy. Therefore, the main aim of this paper is to formulate a typology of militant democracies which would be a useful analytical tool for studying diverse political regimes. Importantly, this paper contributes to the field by proposing the framework of the theory, i.e., militant democracies’ trajectory of continuance which consists of the types of militant democracies and the relationships between them. It is significant to assume that the subjects of militant democracy use offensive and defensive strategies which are characterised by the following degrees of intensity: low, moderate, and high. Hence, nine types of these strategies’ configurations are determined. They generate nine types of militant democracies. Moreover, there are nine factorial relationships between them, which are useful for assessing whether and how empirical exemplifications of political regimes change. This proposal of the typology of militant democracies is highly applicable to empirical studies and worth developing in a theoretical way on the basis of new criteria such as the potential of regime regeneration.
Keywords: demokracja wojująca; system polityczny; zmiana polityczna; potencjał ofensywny; potencjał obronny; typ idealny